Exposures and Health Effects of Diacetyl and 2,3-Pentanedione in a Coffee Processing Facility - Cheung, Kerry; Whitelaw, Jane; Apthorpe, Linda (New Zealand Journal of Health and Safety Practice, 2024)
Diacetyl and 2,3-pentanedione are alpha-diketones that are generated during the coffee roasting process and have been shown to be related to respiratory symptoms, abnormal lung function, and in rare cases, an irreversible disease called obliterative bronchiolitis. This study measured personal exposures in a coffee roastery in New Zealand using thermal desorption tubes and explored the prevalence of respiratory symptoms with a health questionnaire. Exposures from task samples were highest for grinding (Geometric Mean (GM): 22.5 ppb diacetyl; GM: 19.3 ppb 2,3-pentanedione), followed by packaging (GM: 10.8 ppb diacetyl; GM: 9.3 ppb 2,3-pentanedione) and then roasting (GM: 4.7 ppb diacetyl; GM: 4.1 ppb diacetyl). 8-h time-weighted average (TWA) diacetyl exposures exceeded the National Institute of Occupational Safety and Health (NIOSH) Recommended Exposure Limit (REL) of 5 ppb for Roaster/Packager (GM: 6.6 ppb) and Grinder (GM: 5.3 ppb). 8-h TWA concentrations were below the NIOSH REL of 9.3 ppb for 2,3-pentanedione (Roaster/Packager, GM: 5.7 ppb; Grinder, GM: 4.6 ppb). Workers reported nose, eye symptoms and systemic symptoms (flu-like illness or achy joints, fever or chills, or unusual tiredness or fatigue). The results indicated that exposure was highest for tasks involving ground coffee beans and that coffee processing workers can be exposed to alpha-diketones above the NIOSH RELs. Further research into alpha-diketone exposure and health effects, and control measures to minimise exposure are recommended.